Social media activities impact on the decision of watching films in cinema - Montajula Suvattanadilok (My University, 2021)
The aim of the research is to examine the social media activities of film promoters and the factors that have an impact on public decision-making and to watch film in the cinema. This research looked at film audiences in Thailand to evaluate public perception, social media tracking and knowledge-based activity that has not yet been established in previous studies. Few studies have investigated the variables such as promotional programs, social media platform activities, trailer assessment, and decision to watch a movie. This study's audience consisted of Thai citizens who are a sample of 400 subjects. This group has been identified as the group that watched the film in Thailand. The statistical tool used is ANOVA, which is concerned only with the disparity of results used in the comparative analysis. The strongest statistical relationship for the trailer assessment has been identified. Indication of the essential distinction between advertising, social media interactions and trailer assessment. References to social media will motivate the audience to feel that they are enjoying the recommended films. Social awareness is also related to the determination of the reference value for video screening. The findings of this study show that social networks affect audiences to watch movies. Overall, different factors need to work together to inspire audiences to watch movies. In order to make people watch films more frequently in cinemas, it is important to explore other strategies for market demand.
Keywords: Trailer; Sample (material); Value (mathematics); Digital Marketing and Social Media